Curcumin Targeting NF-κB/Ubiquitin-Proteasome-System Axis Ameliorates Muscle Atrophy in Triple-Negative Breast Cancer Cachexia Mice - Zhang, Jin; Zheng, Jin; Chen, Haitao; Li, Xinrong; Ye, Chenxiao; Zhang, Fan; Zhang, Zewei; Yao, Qinghua; Guo, Yong (Mediators of Inflammation, 2022)
Background. Curcumin is a polyphenol plant-derived compound with anti-inflammatory, antioxidant stress, and anticancer properties that make it have the potential to treat cancer cachexia. However, the role of it in breast cancer cachexia remains unclear. Methods. The 4T1 cells were subcutaneously injected into BALB/c mice to induce breast cancer cachexia. After tumor formation, the animals were divided into groups and given curcumin or saline interventions. The therapeutic effect of curcumin on breast cancer cachexia was characterized by tumor growth, changes in body mass and gastrocnemius mass, muscle function test, histopathology, and serum nutrition indexes. Mitochondrial function in muscle tissue was observed by transmission electron microscopy and ATP detection, muscle inflammatory factors were detected by ELISA, muscle differential metabolites were detected by 1HNMR metabolomics, and the muscle tissue ubiquitination levels and NF-KB expression were also analyzed by RT-qPCR and Western blot. Results. Dynamic in vivo bioluminescence imaging find that curcumin inhibited the growth of tumor in triple-negative breast cancer- (TNBC-) bearing mice, slowed down the loss of body weight and gastrocnemius weight, corrected the mitochondrial dysfunction and malnutrition status, and also significantly improved skeletal muscle function. ELISA analysis found that the level of inflammatory factors in muscle tissue was reduced. 1HNMR metabolomics analysis suggested that curcumin could regulate energy metabolism pathways. RT-qPCR and Western blot analysis found that the expression of myogenic factor myogenin was increased and the expression of myodegradation factor myostatin was decreased in the gastrocnemius; the level of ubiquitination and activation of the NF-κB pathway were also declined. Conclusions. Curcumin reduces ubiquitination, inflammation in skeletal muscle by regulating the NF-KB/UPS axis and improves muscle malignant metabolic phenotype and mitochondrial dysfunction, to alleviate muscle atrophy and loss of function in mice with breast cancer cachexia.